2019
DOI: 10.1111/jvim.15613
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic evaluation of calcium oxalate urolithiasis in dogs in the United States: 2010‐2015

Abstract: Background Positive health implications of early recognition of calcium oxalate (CaOx) urolithiasis include increased opportunity for nonsurgical removal, early dietary modification to minimize urolith growth, early removal to avoid urinary obstruction, and early recognition of genetic and metabolic diseases before they contribute to additional morbidity. Objectives To identify high‐ and low‐risk dog breeds for CaOx uroliths and to determine the relationship of age and sex to the development of CaOx uroliths. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 22 publications
3
19
2
1
Order By: Relevance
“…However, this possibility seems unlikely because breed predispositions in our study were similar to those reported by others. 4,6,26 The Standard Poodle, the breed with the highest risk for CaOx-containing uroliths in our study, has been reported as having a predisposition to CaOx urolithiasis in only 2 other studies. 4,5 The Miniature Schnauzer and Bichon Frise have a high risk of CaOx urolithiasis.…”
Section: Discussionmentioning
confidence: 47%
See 2 more Smart Citations
“…However, this possibility seems unlikely because breed predispositions in our study were similar to those reported by others. 4,6,26 The Standard Poodle, the breed with the highest risk for CaOx-containing uroliths in our study, has been reported as having a predisposition to CaOx urolithiasis in only 2 other studies. 4,5 The Miniature Schnauzer and Bichon Frise have a high risk of CaOx urolithiasis.…”
Section: Discussionmentioning
confidence: 47%
“…It has been hypothesized that CaOx formation probably is not associated with hormonal differences in dogs. 26 A significant decrease in the proportion of struvite-containing uroliths was observed from 1985 to 2006. 6 We found no significant change in the proportion of struvite-containing uroliths from 2006 to 2018, with struvite-containing uroliths remaining approximately 43% of total urolith submissions.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Renal tubular epithelial cells is the pivotal cell type that participates in reabsorption and excretion, selectively transport nutrients and metabolic waste [15]. With aging of the companion animals, renal stone has become one of the most common diseases affecting the health of animals [16,17]. However, the mechanism responsible for renal tubular epithelial cell injury during the development of stones has not been fully illuminated.…”
Section: Discussionmentioning
confidence: 99%
“…The recurrence rate after extracorporeal shock-wave lithotripsy in 1 year is 6.70%. This rate can reach up to 41.80% in 5 years (1)(2)(3). Repeated urolithiasis increases the patient's pain and financial burden.…”
Section: Introductionmentioning
confidence: 99%